$$\lim_{x \to \infty}\left(- \cos{\left(6 x \right)} + 1\right) = \left\langle 0, 2\right\rangle$$
$$\lim_{x \to 0^-}\left(- \cos{\left(6 x \right)} + 1\right) = 0$$
Подробнее при x→0 слева$$\lim_{x \to 0^+}\left(- \cos{\left(6 x \right)} + 1\right) = 0$$
Подробнее при x→0 справа$$\lim_{x \to 1^-}\left(- \cos{\left(6 x \right)} + 1\right) = - \cos{\left(6 \right)} + 1$$
Подробнее при x→1 слева$$\lim_{x \to 1^+}\left(- \cos{\left(6 x \right)} + 1\right) = - \cos{\left(6 \right)} + 1$$
Подробнее при x→1 справа$$\lim_{x \to -\infty}\left(- \cos{\left(6 x \right)} + 1\right) = \left\langle 0, 2\right\rangle$$
Подробнее при x→-oo